The pharmacokinetics of conventional and bioenhanced tablet formulations of danirixin (GSK1325756) following oral administration in healthy, elderly, human volunteers - Miller, Bruce E. (Springer International Publishing, 2014)
Danirixin (GSK1325756) is a small, high-affinity, selective and reversible CXCR2 antagonist in development for treatment of chronic obstructive pulmonary disease. The objective of the study was to evaluate the relative bioavailability, including the inter-subject variability, of a conventional immediate-release (IR) formulation and two prototype bioenhanced formulations of danirixin during gastric acid suppression in a healthy, elderly population. A single-centre, crossover study in healthy male and female volunteers aged 65–80 years was conducted. Subjects were randomised to receive danirixin 50 mg IR in the fed and fasted states and danirixin 50 mg Bioenhanced Formulation 1 and 2 in the fasted state. All subjects also received omeprazole 20 mg each morning beginning 4 days prior to the first treatment period and continuing through danirixin dosing in the final treatment period. Twenty subjects were randomised and completed the study. Bioenhanced Formulation 2 in the fasted state demonstrated the highest adjusted geometric means for AUC((0–t)), AUC((0–inf)), AUC((0–24)) and C (max). Danirixin IR demonstrated adjusted means that were higher in the fed state compared with the fasted state. For all formulations tested, there was substantial inter-subject variability (CVb >100 % for all formulations). The overall incidences of adverse events (AEs) were 10 % for danirixin IR (both in the fed and fasted states) and 15–20 % for the bioenhanced formulations. The majority of AEs were mild in intensity. There were no serious AEs. Concomitant use of omeprazole resulted in large inter-subject variability in the exposure to danirixin. Bioenhanced formulation strategies could not overcome the effect of omeprazole on exposure and variability between subjects.